The (14C, 14O) reaction considered as simultaneous pair-exchange or double-charge-exchange processes - Bes, D. R.; Dragún, O.; Maqueda, E. E. (North Holland Publishin Co., 1983)
Fil: Bes, D. R. Comisión Nacional de Energía Atómica; Argentina